2019
DOI: 10.1111/jocn.14845
|View full text |Cite
|
Sign up to set email alerts
|

Development of a suite of metrics and indicators for children’s nursing using consensus methodology

Abstract: Aim and objectives To develop a suite of metrics and indicators to measure the quality of children's nursing care processes. The objectives were to identify available metrics and indicators and to develop consensus on the metrics and indicators to be measured. Background The Office of Nursing and Midwifery Services Director, Health Service Executive, in Ireland established seven workstreams aligned to the following care areas: acute, older persons, children's, mental health, intellectual disability, public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The included articles were performed in six countries, with the highest number (seven) conducted in North America (Connor et al., 2016; Graf, 2011; Kiss & Heiler, 2014; Lacey et al., 2006; Schwalenstocker et al., 2008; Stratton, 2008; Sullivan et al., 2021), three in Australia (Wilson et al., 2012a; Wilson et al., 2012b; Wilson et al., 2013c), and one in each of the following nations: China (Zhang et al., 2017), Ireland (Brenner et al., 2019), Korea (Kim & Kim, 2018), and South Africa (Coetzee et al., 2020). Of all the studies, seven focused on development (Brenner et al., 2019; Coetzee et al., 2020; Graf, 2011; Lacey et al., 2006; Schwalenstocker et al., 2008; Sullivan et al., 2021; Zhang et al., 2017), four focused on validation (Kim & Kim, 2018; Kiss & Heiler, 2014; Wilson et al., 2012a; Wilson et al., 2013c), and three aimed at both development and validation (Connor et al., 2016; Stratton, 2008; Wilson et al., 2012b) of NSOs. Six studies were cohort studies (Graf, 2011; Kim & Kim, 2018; Kiss & Heiler, 2014; Stratton, 2008; Wilson et al., 2012a; Wilson et al., 2013c ) and six were cross‐sectional surveys (Brenner et al., 2019; Connor et al., 2016; Lacey et al., 2006; Schwalenstocker et al., 2008; Wilson et al., 2012b; Zhang et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included articles were performed in six countries, with the highest number (seven) conducted in North America (Connor et al., 2016; Graf, 2011; Kiss & Heiler, 2014; Lacey et al., 2006; Schwalenstocker et al., 2008; Stratton, 2008; Sullivan et al., 2021), three in Australia (Wilson et al., 2012a; Wilson et al., 2012b; Wilson et al., 2013c), and one in each of the following nations: China (Zhang et al., 2017), Ireland (Brenner et al., 2019), Korea (Kim & Kim, 2018), and South Africa (Coetzee et al., 2020). Of all the studies, seven focused on development (Brenner et al., 2019; Coetzee et al., 2020; Graf, 2011; Lacey et al., 2006; Schwalenstocker et al., 2008; Sullivan et al., 2021; Zhang et al., 2017), four focused on validation (Kim & Kim, 2018; Kiss & Heiler, 2014; Wilson et al., 2012a; Wilson et al., 2013c), and three aimed at both development and validation (Connor et al., 2016; Stratton, 2008; Wilson et al., 2012b) of NSOs. Six studies were cohort studies (Graf, 2011; Kim & Kim, 2018; Kiss & Heiler, 2014; Stratton, 2008; Wilson et al., 2012a; Wilson et al., 2013c ) and six were cross‐sectional surveys (Brenner et al., 2019; Connor et al., 2016; Lacey et al., 2006; Schwalenstocker et al., 2008; Wilson et al., 2012b; Zhang et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A flow diagram of the study screening process with reasons for exclusion as categorized by Edinger et al. (2013) is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because clinical nursing practice changes continuously, it is essential to implement measurements of the structure and process of pediatric nursing care quality. However, because Brenner et al 24 confirmed these indicators, the questionnaires developed in 2013 could still be judged as relevant. House et al 4 recognize the importance of implementing measures on structure and process besides outcome measures and adverse events to target areas for improvement.…”
Section: Discussionmentioning
confidence: 99%